Resistance mechanisms and remediation potential of hexavalent chromium in Pseudomonas sp. strain AN-B15 - Yu Shi; Zitong Wang; Huifen Li; Zhengjian Yan; Zhuang Meng; Chang’e Liu; Jinquan Chen; Changqun Duan (Ecotoxicology and Environmental Safety, 2023)
The understanding of bacterial resistance to hexavalent chromium [Cr(VI)] are crucial for the enhancement of Cr(VI)-polluted soil bioremediation. However, the mechanisms related to plant-associated bacteria remain largely unclear. In this study, we investigate the resistance mechanisms and remediation potential of Cr(VI) in a plant-associated strain, AN-B15. The results manifested that AN-B15 efficiently reduced Cr(VI) to soluble organo-Cr(III). Specifically, 84.3 % and 56.5 % of Cr(VI) was removed after 48 h in strain-inoculated solutions supplemented with 10 and 20 mg/L Cr(VI) concentrations, respectively. Transcriptome analyses revealed that multiple metabolic systems are responsible for Cr(VI) resistance at the transcriptional level. In response to Cr(VI) exposure, strain AN-B15 up-regulated the genes involved in central metabolism, providing the reducing power by which enzymes (ChrR and azoR) transformed Cr(VI) to Cr(III) in the cytoplasm. Genes involved in the alleviation of oxidative stress and DNA repair were significantly up-regulated to neutralize Cr(VI)-induced toxicity. Additionally, genes involved in organosulfur metabolism and certain ion transporters were up-regulated to counteract the starvation of sulfur, molybdate, iron, and manganese induced by Cr(VI) stress. Furthermore, a hydroponic culture experiment showed that toxicity and uptake of Cr(VI) by plants under Cr(VI) stress were reduced by strain AN-B15. Specifically, strain AN-B15 inoculation increased the fresh weights of the wheat root and shoot by 55.5 % and 18.8 %, respectively, under Cr(VI) stress (5 mg/L). The elucidation of bacterial resistance to Cr(VI) has an important implication for exploiting microorganism for the effective remediation of Cr(VI)-polluted soils.